How do you solve #y'=-xy+sqrty# given #y(0)=0#?

Answer 1

#y=y(0)=1/4pie^(-1/2x^2)"erfi"^2(1/2x)#

We have #y'=-xy+sqrty# or #dy/dx=y^(1/2)-xy#.
Let #v=y^(1/2)# and #(dv)/dx=1/2y^(-1/2)dy/dx#

Now

#y^(-1/2)dy/dx=1-xy^(1/2)=1-vx#

so

#(dv)/dx=1/2(1-vx)=1/2-1/2vx#
#rArr(dv)/dx+1/2vx=1/2#

This is now a linear first-order ordinary differential equation of the form

#(dv)/(dx)+vP(x)=Q(x)#

We solve this using an integrating factor:

#mu=e^(int1/2xdx)=e^(1/4x^2)#

So the general solution is

#ve^(1/4x^2)=int1/2e^(1/4x^2)dx=1/2(sqrtpi "erfi"(1/2x)+"c")#
Solving for #v#
#v=1/2e^(-1/4x^2)(sqrtpi"erfi"(1/2x)+"c")#
But #v=sqrty# so
#sqrty=1/2e^(-1/4x^2)(sqrtpi"erfi"(1/2x)+"c")#

and

#y=1/4e^(-1/2x^2)(sqrtpi"erfi"(1/2x)+"c")^2#
Now, we have the condition #y(0)=0#

So

#y(0)=1/4e^0(sqrtpi"erfi"(0/2)+"c")^2=0#
#rArr1/4c^2=0rArrc=0#

So the final solution is

#y=y(0)=1/4pie^(-1/2x^2)"erfi"^2(1/2x)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To solve the differential equation ( y' = -xy + \sqrt{y} ) with the initial condition ( y(0) = 0 ), we can use the method of integrating factors.

  1. First, rewrite the equation in the form ( y' + P(x)y = Q(x) ) where ( P(x) = x ) and ( Q(x) = \sqrt{y} ).

  2. Then, find the integrating factor ( \mu(x) = e^{\int P(x) dx} ).

  3. Multiply both sides of the equation by the integrating factor ( \mu(x) ).

  4. Integrate both sides and solve for ( y ).

  5. Apply the initial condition ( y(0) = 0 ) to find the particular solution.

Following these steps:

  1. The equation becomes ( y' + xy = \sqrt{y} ).

  2. The integrating factor is ( \mu(x) = e^{\int x dx} = e^{\frac{x^2}{2}} ).

  3. Multiply both sides by ( \mu(x) ) to get ( e^{\frac{x^2}{2}}y' + xe^{\frac{x^2}{2}}y = \sqrt{y}e^{\frac{x^2}{2}} ).

  4. Integrate both sides with respect to ( x ):

    ( \int e^{\frac{x^2}{2}} y' dx + \int xe^{\frac{x^2}{2}}y dx = \int \sqrt{y}e^{\frac{x^2}{2}} dx ).

  5. Solve the integrals and apply the initial condition ( y(0) = 0 ) to find the particular solution.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7